2022
DOI: 10.1186/s12957-022-02847-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of SWI/SNF complex subunits in undifferentiated gastric carcinoma

Abstract: Background The switch/sucrose nonfermentable (SWI/SNF) complex is an evolutionarily conserved chromatin remodeling complex that displays dysfunction in many tumors, especially undifferentiated carcinoma. Cancer stem cells (CSC), a special type of undifferentiated cancer cells with stem cell-like properties, play an essential role in tumor cell proliferation, invasion, and metastasis. In undifferentiated gastric carcinomas, the association of SWI/SNF complexes with clinicopathological features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…SMARCA4 is associated with progression and poor prognosis in gastric cancer [ 7 , 25 ]. Inactivation of SMARCA4 rarely occurs in classic glandular gastric cancer as a driver molecular event and is more likely to occur in gastric cancer with solid and poorly differentiated and undifferentiated morphology [ 6 , 13 , 16 , 26 ], and loss of SMARCA4 is associated with adverse clinical characteristics [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMARCA4 is associated with progression and poor prognosis in gastric cancer [ 7 , 25 ]. Inactivation of SMARCA4 rarely occurs in classic glandular gastric cancer as a driver molecular event and is more likely to occur in gastric cancer with solid and poorly differentiated and undifferentiated morphology [ 6 , 13 , 16 , 26 ], and loss of SMARCA4 is associated with adverse clinical characteristics [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was easy to invade the adjacent orbital wall and anterior cranial base with an invasive bony reaction, consistent with the image manifestation of case 1 in this paper.SMARCB1 (INI1) and SMARCA4 were in the SWI/SNF complex. The pathogenic mechanism of these tumors is that the gene inactivation mutations or deletions lead to the deletion of the corresponding gene products 10 13 . Schaefer and colleagues suggested that all genes of the SWI/SNF complex, except SMARCB1 and SWI/SNF subunits other than SMARCA4, are rarely involved in head and neck malignancies, and SMARCA4-deficient sinus carcinomas have demographic and clinical features similar to those of SMARCB1-deficient sinus carcinomas.…”
Section: Discussionmentioning
confidence: 99%